Swim the silver sea, Joshie Otter - Carlstrom, Nancy White; Kuroi, Ken, 1947- (New York : Philomel Books, 1993)
Because none of the other animals will play with him, Joshie the sea otter swims too far out to sea, but he is called back by a song sung in the strong safe voice of his mother.
School Library Journal
Booklist
2.7
K-3
Keywords: Sea otter -- Fiction; Otters -- Fiction; Sea otter -- Fiction; Otters -- Fiction